Gulliver - Ryan, Michael (Brooklyn, NY : Autonomedia, 1993)
An allegorical history of the present, Gulliver embarks upon a strange space-age journey of uncanny cultural resemblances and disturbing personal encounters. A political satire that brings us face-to-face with the imperial cannibalism of white capitalist patriarchy and the food chain that constitutes its major social institutions